Competitive interactions between cognitive reappraisal and mentalizing - Powers, John P.; Kako, Nadia; McIntosh, Daniel N.; McRae, Kateri (International journal of psychophysiology, 2022)
To better understand how cognitive context can impact emotion regulation through cognitive reappraisal, we evaluated the effects of an additional mentalizing instruction on reappraisal. This manipulation models an existing therapeutic technique in which a client is instructed to imagine advising a friend in a similar situation. We examined the effects of this manipulation on self-reported affect and difficulty as well as fMRI measures of neural function. We hypothesized that the mentalizing context would facilitate the cognitive processing and performance of reappraisal due to the engagement of common neurocognitive resources across these processes. We trained participants to reappraise negative pictures using reinterpretation, and crossed mentalizing with reappraisal in a within-subjects factorial design. Self-report results indicated that the mentalizing instruction did not impact reappraisal performance. We did, however, identify neural interactions between mentalizing and reappraisal. The particular patterns of interaction suggested that reappraisal processing may have been dominant and mentalizing processing diminished when both were instructed. Overall, our findings suggested that mentalizing and reappraisal did engage shared neurocognitive resources, but this overlap resulted in competition between these processes rather than facilitation. We discuss potential mechanisms and identify directions for future research. This study was preregistered at https://osf.io/ym28u/. •Impacts on reappraisal of a cognitive context relevant to therapeutic practice•Competitive neural interactions between related cognitive processes•Online and retrospective self-reports of affect and perceived difficulty